Alpheus luiszapatai, a new species of rare and colorful deep water alpheid shrimp (Crustacea: Decapoda: Alpheidae) from Arusí, Chocó Department, Pacific Coast of Colombia - Ramos-Tafur, Gabriel E. (Zootaxa, 2018)
A new species of deep water alpheid shrimp, Alpheus luiszapatai sp. nov., from Arusí, Chocó, Pacific coast of Colombia is described. The single female known was collected between the discarded bycatch of deep water shrimp trawls dedicated to the commercial fisheries of the “coliflor” shrimp Solenocera spp. This new species is placed putatively in the Alpheus brevirostris (Olivier, 1811) species group, and share some external morphological characters with Alpheus hephaestus Bracken-Grissom & Felder, 2014. It can be differentiated by the shape and ornamentation of major and minor chelipeds, the propodi and dactyli of third to fifth pereopods, the diaresis of uropodal exopod, the length of the rostral carina, color in life and bathymetric distribution. Additional comparison with another congeners pertaining to this species group complex from the eastern Pacific, western Atlantic and other oceanographic regions is discussed. A key for Alpheus brevirostris species group from the eastern Pacific is presented.